Elevated Autoantibodies in Subacute Human Spinal Cord Injury Are Naturally Occurring Antibodies - Arevalo-Martin, Angel; Grassner, Lukas; Garcia-Ovejero, Daniel; Paniagua-Torija, Beatriz; Barroso-Garcia, Gemma; Arandilla, Alba G.; Mach, Orpheus; Turrero, Angela; Vargas, Eduardo; Alcobendas, Monica; Rosell, Carmen; Alcaraz, Maria A.; et al. (Frontiers in Immunology, 2018)
Spinal cord injury (SCI) results in long-term neurological and systemic consequences, including antibody-mediated autoimmunity, which has been related with impaired functional recovery. Here we show that autoantibodies that increase at the subacute phase of human SCI, one month after lesion, are already present in healthy subjects and directed against non-native proteins rarely present in the normal spinal cord. The increase of these autoantibodies is a fast phenomenon –their levels are already elevated before 5 days after lesion– characteristic of secondary immune responses, further supporting their origin as natural antibodies. By proteomics studies we have identified that the increased autoantibodies are directed against 16 different nervous system and systemic self-antigens related with changes known to occur after SCI, including alterations in neural cells cytoskeleton, metabolism and bone remodelling. Overall, in the context of previous studies, our results offer an explanation to why autoimmunity develops after SCI and propose novel targets involved in SCI pathology that warrant further investigation.